The gameshouse - North, Claire (Orbit, 2019)
Everyone has heard of the Gameshouse. But few know all its secrets... It is the place where fortunes can be made and lost through chess, backgammon - every game under the sun. But those whom fortune favors may be invited to compete in the higher league... a league where the games played are of politics and empires, of economics and kings. It is a league where Capture the Castle involves real castles, where hide and seek takes place on the scale of a continent. Among those worthy of competing in the higher league, three unusually talented contestants play for the highest stakes of all...